Measurement of Mass Transfer Intensity in Gas–Liquid Medium of Bioreactor Circuit Using the Thermometry Method - Starodumov, Ilya; Nizovtseva, Irina; Lezhnin, Sergey; Vikharev, Sergey; Svitich, Vladislav; Mikushin, Pavel; Alexandrov, Dmitri; Kuznetsov, Nikolay; Chernushkin, Dmitri (Fluids (Basel), 2022)
The development of energy-efficient solutions for large-scale fermenters demands a deep and comprehensive understanding of hydrodynamic and heat and mass transfer processes. Despite a wide variety of research dedicated to measurements of mass transfer intensity in bubble flows, this research subject faces new challenges due to the topical development of new innovative bioreactor designs. In order to understand the fluid dynamics of the gas–liquid medium, researchers need to develop verified CFD models describing flows in the bioreactor loop using a progressive physical and mathematical apparatus. In the current paper, we represent the results of evaluating the key performance indicator of the bioreactor, namely the volumetric mass transfer coefficient (kLa) known as a parameter of dominant importance for the design, operation, scale-up, and optimization of bioreactors, using the developed thermometry method. The thermometry method under consideration was examined within a series of experiments, and a comparative analysis was provided for a number of various regimes also being matched with the classical approaches. The methodology, experiment results, and data verification are given, which allow the evaluation of the effectiveness and prediction of the fluid flows dynamics in bioreactors circuits and ultimately the operational capabilities of the fermenter line.